The Implementation Management of Inclusive Education Programs at SDN 002 Pulau Palas, Tembilahan Hulu, Indragiri Hilir Regency - Melia, Linda (Perspektif Pendidikan dan Keguruan, 2022)
The purpose of this study was to analyze the implementation of Inclusive Education Management at SD Negeri 002 Pulau Palas, including: 1) Education planning, 2) Education implementation, 3) Education evaluation, and 4) Supporting and inhibiting factors for education management of Students with Special Needs (SwSN) at SD Negeri 002 Pulau Palas. The method used in this study is a qualitative descriptive method. It was conducted at SD Negeri 002 Pulau Palas. The subjects of this study included: 1 principal, 1 class teacher, 1 special assistant teacher, and 1 student's parent, hhich was in August 2022. The Data were collected through observation, interviews, and document review techniques. After gathering the data, the researchers analyzed them qualitatively. The research results on inclusive education management at SD Negeri 002 Pulau Palas which are currently running in accordance with regulations with planning on the curriculum that contains the vision and mission of SD Negeri 002 Pulau Palas. It uses the K-13 curriculum by modifying the lesson plans, materials, learning media, and learning evaluation in study groups that have SwSN according to their disabilities. The SwSN in SDN 002 Pulau Palas in 2022 there are 24 students with details of disabilities. Supporting factors for the implementation of education for children with special needs at SDN 002 Pulau Palas are schools still implementing inclusive education programs, there are students with special needs in schools, financial assistance from the central government, teachers teachers consistently carry out their duties and functions, adequate learning media are available, communication with parents is quite good. While the inhibiting factors are the lack of special supervisory teachers, teachers have never attended training, there are still parents who do not care about inclusive education programs, and learning media are still lacking.